MANAJEMEN PAJAK, DARI AWAL SAMPAI AKHIR - Yoseph Agus BBN (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
Tax management in Indonesia actually is not a new issue. While taxpayers in other countries comply their taxes objectively and fairly, Indonesian taxpayers are struggling to put their right properly. In this circumstances, tax management is badly needed. At the starting point of forming a firm, tax implementation, appeal and tax court, tax management should be designed based on professionals maners. Finally, at the closing phase, taxmanagement should be conducted comprehensively within integration of overall managerial activities.